2014
DOI: 10.1093/jnci/dju115
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Patient Navigation on Timely Cancer Care: The Patient Navigation Research Program

Abstract: Patient navigation demonstrated a moderate benefit in improving timely cancer care. These results support adoption of patient navigation in settings that serve populations at risk of being lost to follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
207
1
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 227 publications
(218 citation statements)
references
References 40 publications
(42 reference statements)
3
207
1
1
Order By: Relevance
“…A common provider barrier to screening in underserved communities is an inadequate referral mechanism after an abnormal test (46). Patient navigators or community health workers are particularly beneficial for facilitating follow-up and treatment in underserved populations (47).…”
Section: Discussionmentioning
confidence: 99%
“…A common provider barrier to screening in underserved communities is an inadequate referral mechanism after an abnormal test (46). Patient navigators or community health workers are particularly beneficial for facilitating follow-up and treatment in underserved populations (47).…”
Section: Discussionmentioning
confidence: 99%
“…It is incumbent on the medical community to be aware of and make explicit efforts to increase trust and minimize the potential effects of perceived power imbalances (40). Patient/family advisory boards, dialysis team training, and use of patient navigators (41), as one patient suggested, could ultimately improve ACP thorough improved communication and trust.…”
Section: Discussionmentioning
confidence: 99%
“…Access to, and continuity of, primary care, the use of medical oncology and chemotherapy [18][19][20]22 , and being a nursing home resident 19,23,30 are also relevant. Socioeconomic and distance indicators of inequity should be investigated by linking the postal code of residence at death to census data 17,19,22,23,45 because a meta-analysis showed that the benefit from navigation is greatest for the most vulnerable individuals 46 .…”
Section: Strengths Limitations and Recommendationsmentioning
confidence: 99%